Cardiovascular-Related Death Risk Factors in Hypertensive Patients: Indonesia Family Life Survey 2000-2014 - Rudi Supriyadi; David Paranoan; Yulia Sofiatin (Faculty of Medicine Universitas Padjadjaran, 2021)
Objective: To determine the characteristics of the risk factors of cardiovascular death in hypertensive patients in Indonesia based on the Indonesian Family Life Survey (IFLS) longitudinal data. Methods: This was a retrospective descriptive study on secondary data from the IFLS population starting from2000 and was followed up in 2007 and 2014. The inclusion criteria for participation were15 years old or older, had hypertension, had cardiovascular events as thecause of death, and had complete data in both IFLS 3 (2000) and IFLS 4 (2007).Results: The IFLS 5 (2014) reported 918 deaths among eligible subjects with complete data, both in IFLS 3 (2000) and IFLS 4 (2007). Of those, a total of 608 subjects experienced hypertension started from 2000 and/or 2007. Of these deaths, 112 were due to cardiovascular events. Cardiovascular death was more common in males (58.9%), age of >65 years old when died (47.3%), had poor socioeconomic status (24.1%), and with normal body mass index (54.9%).Conclusion: Male, late adulthood, low level of education, normal BMI, and poor socioeconomic status represented the greater risks of cardiovascular death among hypertensive patients in Indonesia.